(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
The current study sought to identify the level of support provided for first year university students during the novel COVID-19 pandemic online classes with the Moodle learning management system (LMS). The researchers surveyed 1416 first year university students in the second semester of the 2019/2020 academic year, who were all supposed to be part of the web-based courses to logically bring the semester to an end. In an attempt to make students become familiar with the use of the Moodle LMS, the university introduced measures like online orientation, creation of instructional videos, provision of hot phone contact lines as well as IT centre support. Out of these interventions rolled-out by the university, the researchers found that the students did not gain the required benefits as envisaged by the University and for that matter affected the students adversely. From an instructional standpoint, the measures put in place to familiarize students with the Moodle system were laudable. However, the support services provided had issues of implementation. A need exists for a more comprehensive and coordinated support services to adequately equip university students to participate meaningfully in web-based learning.